2003
DOI: 10.1016/s1534-5807(03)00090-x
|View full text |Cite
|
Sign up to set email alerts
|

Annexin I Is an Endogenous Ligand that Mediates Apoptotic Cell Engulfment

Abstract: Engulfment of apoptotic cells requires presentation of new cell surface ligands by the dying cells. Using a differential proteomics technology, we identify that annexin I is a caspase-dependent engulfment ligand; it is recruited from the cytosol and exported to the outer plasma membrane leaflet, colocalizes with phosphatidylserine, and is required for efficient clearance of apoptotic cells. Furthermore, phosphatidylserine receptor (PSR) clustering around apoptotic cells indicates a requirement for annexin I. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
287
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(301 citation statements)
references
References 48 publications
9
287
1
4
Order By: Relevance
“…Finally, the membrane expression of ANXA1 after 24 h TRAIL (Figure 1c) confirms previous results in Jurkat cells 5 and suggests that the exposure of ANXA1 on the surface of apoptotic cells may be a widespread mechanism for the recognition and removal of apoptotic cells not restricted to a single cell type. Further work is necessary to clarify the role of ANXA1 as 'eat me' signal in FRO cells.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Finally, the membrane expression of ANXA1 after 24 h TRAIL (Figure 1c) confirms previous results in Jurkat cells 5 and suggests that the exposure of ANXA1 on the surface of apoptotic cells may be a widespread mechanism for the recognition and removal of apoptotic cells not restricted to a single cell type. Further work is necessary to clarify the role of ANXA1 as 'eat me' signal in FRO cells.…”
supporting
confidence: 89%
“…Importantly, silencing ANXA1 protein by small interference RNA (siRNA) resulted in defective tethering and engulfment of apoptotic cells. 5 Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a member of the tumor necrosis factor (TNF) family of proteins including FasL, and TNF-a. TRAIL effectively kills most thyroid cancer cell lines tested, including those originating from anaplastic carcinomas.…”
mentioning
confidence: 99%
“…Recently, it has been suggested that calreticulin may function as a second general recognition ligand, via binding and activating LRP or CD91 on engulfing cells. 14 Arur et al 37 have suggested that annexin I may function in the facilitation of or enhancement of the recognition of PS by the receptor. Whether calreticulin or annexin I is related to stabilin-2-mediated phagocytosis is currently unclear, and will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of membrane components in CN and CS conditions may provide more clues about the molecular mechanism of larval arrest upon CS. Furthermore, NEX-1 functions as a ligand that mediates efficient clearance of apoptotic cells by colocalizing with phosphatidylserine (Arur et al, 2003). Therefore, up-regulation of NEX-1 is likely to promote engulfment of cell corpses generated by developmental defects.…”
Section: Discussionmentioning
confidence: 99%